2006
DOI: 10.1016/j.jhsb.2005.09.022
|View full text |Cite
|
Sign up to set email alerts
|

Revision Surgery after Carpal Tunnel Release –Analysis of the Pathology in 200 Cases during a 2 Year Period

Abstract: Carpal tunnel release (CTR) is regarded as a common and successful operative procedure in hand surgery. However, an increasing number of patients with complications have been referred to our hospital. This retrospective investigation was undertaken to clarify the reasons for persisting or recurrent symptoms in 200 patients who underwent secondary exploration during a 26 month period at a single institution. In 108 cases, the flexor retinaculum was found to have been released incompletely. In 12 patients, a ner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
80
0
12

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(95 citation statements)
references
References 25 publications
3
80
0
12
Order By: Relevance
“…Consistent with existing literature (2, 13), nerve injury was almost exclusively seen in patients presenting with new CTS. Inadvertent transection of the superficial median fascicles, the third common digital nerve, and median nerve PCB were most common, as in the study by Stutz et al (12). While relatively uncommon, inadvertent nerve injury during CTR can be devastatingly life-altering for the patient, and the importance of excellent visualization and a cautious, methodical approach to CTR cannot be overstated.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Consistent with existing literature (2, 13), nerve injury was almost exclusively seen in patients presenting with new CTS. Inadvertent transection of the superficial median fascicles, the third common digital nerve, and median nerve PCB were most common, as in the study by Stutz et al (12). While relatively uncommon, inadvertent nerve injury during CTR can be devastatingly life-altering for the patient, and the importance of excellent visualization and a cautious, methodical approach to CTR cannot be overstated.…”
Section: Discussionmentioning
confidence: 94%
“…Persistent CTS refers to the persistence of preoperative symptoms following carpal tunnel release with little or no improvement. Of the complications following CTR, persistence is the most common and is often due to incomplete release of the flexor retinaculum or to incorrect diagnosis (2,12,13). Recurrent CTS refers to when the primary release was successful in relieving symptoms, but similar symptoms recur after a period of months or years.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the drawbacks of ECTR is the incomplete release of the TCL (17). This can be easily and effectively resolved if the endoscope is inserted into the carpal tunnel from the entry portal and the stumps of the TCL are confirmed from proximal end toward the distal end.…”
Section: Discussionmentioning
confidence: 99%
“…19 Another study found that most postsurgical complications may be attributed to technical errors during the initial procedure. 20 The presence of CTS with ganglion cysts has been shown to result in deafferentation and motor deficits. Twelve cases of ganglion cysts and CTS were reported, with 8 cases demonstrating abnormal motor conduction or distal sensory latencies.…”
Section: Introductionmentioning
confidence: 99%